Macro-scale transport of the excitation energy along a metal nanotrack: exciton-plasmon energy transfer mechanism - Khmelinskii, Igor (2019)
Presently we report (i) excited state (exciton) propagation in a metal nanotrack over macroscopic distances, along with (ii) energy transfer from the nanotrack to adsorbed dye molecules. We measured the rates of both of these processes. We concluded that the effective speed of exciton propagation along the nanotrack is about 8 × 107 cm/s, much lower than the surface plasmon propagation speed of 1.4 × 1010 cm/s. We report that the transmitted energy yield depends on the nanotrack length, with the energy emitted from the surface much lower than the transmitted energy, i.e. the excited nanotrack mainly emits in its end zone. Our model thus assumes that the limiting step in the exciton propagation is the energy transfer between the originally prepared excitons and surface plasmons, with the rate constant of about 5.7 × 107 s-1. We also conclude that the energy transfer between the nanotrack and the adsorbed dye is limited by the excited-state lifetime in the nanotrack. Indeed, the measured characteristic buildup time of the dye emission is much longer than the characteristic energy transfer time to the dye of 81 ns, and thus must be determined by the excited state lifetime in the nanotrack. Indeed, the latter is very close to the characteristic buildup time of the dye emission. The data obtained are novel and very promising for a broad range of future applications.